2019
DOI: 10.1186/s12866-019-1454-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an NDM-5 carbapenemase-producing Escherichia coli ST156 isolate from a poultry farm in Zhejiang, China

Abstract: Background The emergence of carbapenem-resistant Enterobacteriaceae strains has posed a severe threat to public health in recent years. The mobile elements carrying the New Delhi metallo-β-lactqtamase (NDM) gene have been regarded as the major mechanism leading to the rapid increase of carbapenem-resistant Enterobacteriaceae strains isolated from clinics and animals. Results We describe an NDM-5-producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 64 publications
5
28
1
Order By: Relevance
“…The presence of carbapenem resistance in bacteria from animals, including food-producing animals (pigs, bovines and horses) has also been reported from some European countries such as Germany, France and Belgium [9]. The identification of E.coli isolates harbouring multiple (at least two) carbapenemase encoding genes from food animal in this study differentiates it from previous similar studies which mostly reported E. coli isolates harbouring one or two carbapenemase genes [11,12].…”
Section: Discussionsupporting
confidence: 60%
“…The presence of carbapenem resistance in bacteria from animals, including food-producing animals (pigs, bovines and horses) has also been reported from some European countries such as Germany, France and Belgium [9]. The identification of E.coli isolates harbouring multiple (at least two) carbapenemase encoding genes from food animal in this study differentiates it from previous similar studies which mostly reported E. coli isolates harbouring one or two carbapenemase genes [11,12].…”
Section: Discussionsupporting
confidence: 60%
“…3). BLASTn analysis revealed high similarity (100% query cover and 99% nucleotide identity) to previously reported bla NDM−5 -positive plasmids, including the bla NDM−5 -positive plasmids of various sources, such as MH234502 (human, China) [9], CP027204 (sewage, China) [9], CP029245 (laying hen, China) [9], CP028705 (vegetable, China) [9], KX507346 (swine, China) [9], and CP034744 (goose, China) [9]. Comparative analysis revealed that these plasmids are highly similar, possessing the same backbone, which includes IncX3 replication.…”
Section: Conjugationsupporting
confidence: 51%
“…WGS showed that E. coli 15978 and C4109 belonged to ST156 and ST167, respectively ( Table 1). These two E. coli sequence types were also related to bla NDM dissemination worldwide in humans, 15,16 animals, 17,18 and food. 19 The resistance genes, chromosomal mutations, and virulence genes of the two isolates were displayed in Table 1.…”
Section: Resultsmentioning
confidence: 90%